2017
DOI: 10.1002/asjc.1633
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Fractional Order PI Controller Design for a Flexible Swing arm System Via Enhanced Virtual Reference Feedback Tuning

Abstract: Flexible swing arm system (FSAS) is one of the most important components in the LED packaging industry. The trajectory tracking performance of the FSAS will directly affect the efficiency and accuracy of the LED packaging equipment. In order to meet the high precision and high speed requirements, this paper proposes an adaptive fractional order proportional integral (AFOPI) control method based on enhanced virtual reference feedback tuning (EVRFT). In this method, the AFOPI controller is applied to handle the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Fractional calculus is an old branch of mathematics that dates back since the early foundations of conventional integer-order calculus, three centuries ago. Nonetheless, the very first engineering applications of fractional-order tools were made available in last decades [1][2][3][4][5][6]. Furthermore, the study of nonlinear effects, as well as the implementation of non-smooth techniques in observation and stabilisation of fractional-order systems has been addressed in recent years [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus is an old branch of mathematics that dates back since the early foundations of conventional integer-order calculus, three centuries ago. Nonetheless, the very first engineering applications of fractional-order tools were made available in last decades [1][2][3][4][5][6]. Furthermore, the study of nonlinear effects, as well as the implementation of non-smooth techniques in observation and stabilisation of fractional-order systems has been addressed in recent years [7].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling a plant is an approximation of the real system with unmodeled dynamics and parametric uncertainties, and therefore the resulting path-tracking errors of model-based methods cannot converge to a small attenuation level if the identified model is inaccurate. Moreover, recent studies have revealed inherent fractional-order features in the servo drive systems, which increases the difficulties to design a model-based cascade controller for such servo-controlled robots [19], [20]. Another underlying problem is that the existing cascade controllers are usually tuned sequentially via different techniques, i.e., the inner secondary controller is tuned first to give a faster tracking response, followed by the optimization of the outer primary controller [21].…”
Section: Introductionmentioning
confidence: 99%
“…viscoelastic systems [12], electrochemistry [13,14], thermal systems and heat conduction [15][16][17], mechanical systems [18] and biology [19]. Furthermore, fractional-order controllers have been implemented to enhance the robustness and the performance of closed-loop control systems [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%